2010
DOI: 10.1257/jep.24.4.67
|View full text |Cite
|
Sign up to set email alerts
|

Natural Expectations and Macroeconomic Fluctuations

Abstract: A large body of empirical evidence suggests that beliefs systematically deviate from perfect rationality. Much of the evidence implies that economic agents tend to form forecasts that are excessively influenced by recent changes. We present a parsimonious quasi-rational model that we call natural expectations, which falls between rational expectations and (na�ve) intuitive expectations. (Intuitive expectations are formed by running growth regressions with a limited number of right-hand-side variables, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
157
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(171 citation statements)
references
References 72 publications
14
157
0
Order By: Relevance
“…Branch (2006) gives an excellent survey and argues that RPE is a natural alternative to rational expectation equilibrium, because it is to some extent consistent with Muth's original hypothesis of REE while allowing for bounded rationality by restricting the class of perceived laws of motion. Fuster et al (2010) and Fuster et al (2011Fuster et al ( , 2012 propose a concept of natural expectations, where agents use simple, misspecified models, e.g., linear autoregressive models, for their perceived law of motion. They argue that economists and non-economists -statisticians, professional forecasters, and firms-regularly make some simplifications of models.…”
Section: Introductionmentioning
confidence: 99%
“…Branch (2006) gives an excellent survey and argues that RPE is a natural alternative to rational expectation equilibrium, because it is to some extent consistent with Muth's original hypothesis of REE while allowing for bounded rationality by restricting the class of perceived laws of motion. Fuster et al (2010) and Fuster et al (2011Fuster et al ( , 2012 propose a concept of natural expectations, where agents use simple, misspecified models, e.g., linear autoregressive models, for their perceived law of motion. They argue that economists and non-economists -statisticians, professional forecasters, and firms-regularly make some simplifications of models.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of agents developing irrational beliefs in this context quickly comes to mind (e.g., Glaeser and Nathanson, 2015). Various studies demonstrate that people do not readily forecast mean reversion processes of variables that grow sustainably over quite a long period (Fuster et al, 2010), which is what occurred in our case.…”
Section: Myopic Politicianmentioning
confidence: 56%
“…They found that analysts tend to systematically misinterpret new information about the investment; they underreact to negative information, but overreact to positive information. The issue of misinterpreting new information and past historical changes is also one of the main explanations of excessive optimism in works of Fuster, Herbert, and Laibson (2011;2012) and Fuster, Laibson, and Mendel (2010). In these papers, the authors suggest that in the process of predicting future prices of assets or markets, subjects use both rational analytic strategies and more simplex heuristic models, which fasten the reasoning about the dynamics of fundamental economic factors.…”
Section: Excessive Optimism Of Investment Managers and Financial Analmentioning
confidence: 99%